The Nurse, the Veteran, and the Female Scientist: Dependency and Separation - Kirsten Twelbeck (European Journal of American Studies)
The discourse that emerged around the female nurses who served in American Civil War hospitals has been a major topic in the debate about nineteenth-century gender relations. What remains obscure, however, is the genesis of this figure during the postwar period and its influence on late nineteenth-century gender relations. Focusing on the post-1865 period as a time of emotional crisis and mental adaptation (Leslie Butler), this article seeks to analyze and assess the gendered tensions that emerged when the process of “binding up the nation’s wounds” (Abraham Lincoln) became a more permanent occupation than was commonly anticipated. By reading Louisa May Alcott’s Hospital Sketches, Silas Weir Mitchell’s “The Case of George Dedlow,” Alonzo F. Hill’s John Smith’s Funny Adventures on a Crutch, and Mary Bradley Lane’s Mizora as contributions to and critical interventions into official veteran memorial culture, this article sheds light on the gendered dimension of the Reconstruction adaptation and negotiation process, and explains why the concept of the female nurse played a crucial role in this development.